The Euro's effect on trade: An analysis of "old" and "new" EMU members - Isaac Mensah (FIW - Research Centre International Economics, 2017)
This paper provides new empirical evidence of the "euro effect" on bilateral trade by allowing for a heterogeneous impact on "new" and "old" EMU members. By applying a Poisson estimator and focusing on a sample of 38 countries, our results show a statistically insignificant euro's effect on bilateral exports. However, disaggregating this effect, we report a relatively large euro's effect on bilateral trade for the "new" EMU countries. We also and no evidence of trade diversion, thus corroborating existing evidence. These results are robust to a number of sensitivity checks and, especially, to the use of a larger sample of countries.
Keywords: F4; F14; F15; F33; C33; 330; Gravity model; Bilateral exports; Euro; Poisson estimator